IMPROVING POSYANDU SERVICE PERFORMANCE THROUGH THE USE OF SMARTPHONE APPLICATIONS: LITERATURE REVIEW - Tanwir Djafar , Sukri Palutturi, Andi Zulkifli, Anwar Mallongi, Ida Leida, Suriah, (Chelonian Research Foundation, 2024)
Introduction: Posyandu, or Integrated Service Post, is the government's effort to make maternal and child health services more accessible to Indonesians. This literature review aims to identify and describe the performance of posyandu services using smartphone applications, Method: The research method is a systematic review using techniques such as PICOT and journal search terms via MESH. The literature sources in this study mostly come from online journal databases that provide Indonesian and English journal articles in PDF format, such as Pubmed, Proquest, Google Scholar, and ScienceDirect, as well as other sources, such as books. Researchers wrote keywords according to MESH (Medical Subject Heading), namely "service", "smartphone", and "posyandu," and selected full text. Research result: Of the 120 journals that reviewed the abstracts, there are 20 journals consisting of review journals and journals related to the use of smartphones in posyandu services. So, the 10 remaining journals will be read in full-text Discussion: Smartphones are modern technological devices that make it easier to communicate, obtain information, and do work quickly and comprehensively. The use of smartphones in the world of health is considered effective in increasing access to health services, especially posyandu services. Conclusion: The use of smartphones and applications in posyandu services accelerates the achievement of targets in the form of posyandu and is effective in increasing access to health services.